Lemna turionifera Landolt (Araceae) — новий вид флори України - Орлов, О.О.; Якушенко, Д.М. (Український ботанічний журнал, 2013)
Приводится информация о морфологических, хорологических и эколого-ценотических особенностях нового для флоры Украины вида — Lemna turionifera Landolt. Кратко обсуждается его статус во флоре страны. Впервые для изученной
территории отмечены сообщества ассоциации Lemnetum minori-
turioniferaе. The article provides information on morphological, chorological,
ecological and coenotic features of a new species for the flora of
Ukraine, Lemna turionifera Landolt. The status of this species in
the flora of the country is briefly discussed. Communities of the
association Lemnetum minori-turioniferae are reported for the
study area for the first time.